(untitled) (مجلة أبحاث قانونية, 2023)
Arbitration has the nature of convention; especially in its formation stage- arbitration is a contract. This nature casts its shadow over the arbitration agreement and subjugates it to its principles, on top of which is the principal of “The limited scope of Contract Enforcement”. However, the legislator seems to depart from this principle in many occurrences. In addition, economic developments and their complex contractual formulas have made it necessary for the legislator to leave behind this principle in more than one occasion. From this standpoint, this research will discuss the most important practical cases that represent an exception to the principle of the Limited Scope of Contract Enforcement. Key Words: Outreach of Arbitration Clause, Limited Scope of Contract Enforcement, Group of Contracts, Group of Companies.